Evaluating Peer Tutoring for Reproductive Health Education: A Study in Palu, Indonesia - Hamidah Hamidah; Nur Afni Imbran; Juniardi Juniardi; Budiman Budiman; Muh. Jufri (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: This research aims to determine the use of peer mentoring as a means of reproductive health education for adolescents in Palu City. Method: The research is This research is quantitative research involving secondary school students by developing reproductive health education methods that are more appropriate and effective in increasing adolescents' knowledge and attitudes towards reproductive health in the Palu city. Results: This research shows that peer tutoring is effective in increasing students' knowledge, but is not yet effective in improving students' attitudes about reproductive health. Research Implications: Peer mentoring can be used as an alternative method for reproductive health education in schools and has the potential to be further developed and researched to achieve long-term effects on student behavior. Conclusion:Peer conversation can be used as an educational means to increase students' knowledge about reproductive health.